Historical overview of long-distance signalling in plants - Kondhare, Kirtikumar R.; Patil, Nikita S.; Banerjee, Anjan K. (Journal of Experimental Botany, 2021)
Be it a small herb or a large tree, intra- and intercellular communication and long-distance signalling between distant organs are crucial for every aspect of plant development. The vascular system, comprising xylem and phloem, acts as a major conduit for the transmission of long-distance signals in plants. In addition to expanding our knowledge of vascular development, numerous reports in the past two decades revealed that selective populations of RNAs, proteins, and phytohormones function as mobile signals. Many of these signals were shown to regulate diverse physiological processes, such as flowering, leaf and root development, nutrient acquisition, crop yield, and biotic/abiotic stress responses. In this review, we summarize the significant discoveries made in the past 25 years, with emphasis on key mobile signalling molecules (mRNAs, proteins including RNA-binding proteins, and small RNAs) that have revolutionized our understanding of how plants integrate various intrinsic and external cues in orchestrating growth and development. Additionally, we provide detailed insights on the emerging molecular mechanisms that might control the selective trafficking and delivery of phloem-mobile RNAs to target tissues. We also highlight the cross-kingdom movement of mobile signals during plant-parasite relationships. Considering the dynamic functions of these signals, their implications in crop improvement are also discussed.
Keywords: Long-distance signalling; mobile RNAs; phloem; plasmodesmata; RNA-binding proteins; small RNAs